2020
DOI: 10.1103/physrevlett.124.027202
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Switching of Tristate Antiferromagnetic Néel Order in αFe2O3 Epitaxial Films

Abstract: These two authors contributed equally to this work. The ability to manipulate antiferromagnetic (AF) moments is a key requirement for the emerging field of antiferromagnetic spintronics. Electrical switching of bi-state AF moments has been demonstrated in metallic AFs, CuMnAs and Mn 2 Au. 1-5 Recently, current-induced "saw-tooth" shaped Hall resistance was reported in Pt/NiO bilayers, 6-9 while its mechanism is under debate. Here, we report the first demonstration of convincing, non-decaying, steplike electric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 41 publications
8
75
1
Order By: Relevance
“…This sawtooth-like nature also persists for various τ P and t PtMn (see supplementary Fig. S5(b)-(d)), and closely resembles the switching characteristics observed in some previous works 40,41 . The present results suggest the existence of different driving forces, manifesting in distinct R Hall characteristics of PtMn with/without the HM layer.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This sawtooth-like nature also persists for various τ P and t PtMn (see supplementary Fig. S5(b)-(d)), and closely resembles the switching characteristics observed in some previous works 40,41 . The present results suggest the existence of different driving forces, manifesting in distinct R Hall characteristics of PtMn with/without the HM layer.…”
Section: Resultssupporting
confidence: 88%
“…For a polycrystalline textured PtMn, these estimates intuitively imply the possible existence of an inhomogeneous multi-domain antiferromagnetic ground state configuration with a partial or dominant easy-plane magnetic anisotropy contribution, accounting for the observed 90°s witching. Next, we discuss the effect of possible interactions namely, the bulk or interfacial SOTs generated by spin-Hall effect in HM layer [22][23][24]26 , Néel SOTs specific to the AFM [37][38][39] , spin-transfer torque (STT) generated by spin-polarized conduction electrons in the AFM layer 55,56 , and thermal activation of antiferromagnetic grains 20,41 due to the effect of Joule heating. Owing to the negligible current flow through the oxidized Ru capping layer, we do not consider its contribution for both PtMn/Pt and PtMn/Ru structures.…”
Section: Discussionmentioning
confidence: 99%
“…consistent with the data obtained from the transport experiments presented in Refs. [12,13], where a change of R ⊥ is observed in Pt films. However, we interpret this observation as a local variation of the film resistivity which gives rise to a R ⊥ change R ⊥ with alternating sign for the different pulsing directions.…”
Section: Introductionmentioning
confidence: 94%
“…1(a). In this type of experiments, Cheng et al identified a "saw-tooth"-shaped contribution in R ⊥ measurements arising from the Pt layer for large current density [12], which is of nonmagnetic origin. It was found to be larger than the magnetic contribution to the transverse electrical response in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…In the existing emergent memory devices, oxygen redox effect, [1][2][3] nanofilament formation, [4][5][6][7] phase transition, [8][9][10] spin switching, [11][12][13][14][15][16] and ferroelectric switching [17][18][19] have been widely exploited to alter the resistance state. Recently, in the category of spin switching memory, memory bit cells based on antiferromagnet (AFM) have drawn increasing attentions by showing prospects of As numerous chemical and physical changes could be triggered by the electrical current injection, [34,38] it is of crucial importance to examine the correlation between the switching and the spin-related properties of the bilayer to unambiguously identify the spin-orbit torque driven Néel order switching in AFMI/Pt. These examinations could also greatly facilitate the design of AFMI/Pt-based memristor devices.…”
Section: Introductionmentioning
confidence: 99%